Evaluating rural roads programmes: A general equilibrium analysis - Clive Bell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The structure employed is a small open economy, with one city and a rural hinterland, two traded goods, a transport sector, two specific factors, and mobile labour. A socially profitable programme will promote not only internal, but also external trade. Theory and numerical examples indicate that aggregate social profitability and its distribution between town and country are rather insensitive to the city's location and whether: (i) it is financed by a tariff or an excise on the importable; (ii) the transportation wage is regulated; and (iii), when agents are risk neutral, the economy's barter terms of trade fluctuate stochastically
Keywords: H54; O18; O22; R13; 330; rural roads; general equilibrium; social profitability; small open economy